2023
DOI: 10.1210/clinem/dgac748
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Thyrotropin Levels and Thyroid Function at Early Gestation in Women With Hashimoto Thyroiditis

Abstract: Context Preconception optimization of thyroid function in women with Hashimoto’s thyroiditis (HT) is highly recommended to prevent/reduce the risk of thyroid insufficiency at early gestation. Objectives To evaluate the prevalence of 1st-trimester thyroid insufficiency in HT women with preconception thyrotropin (T0-TSH) values consistently ≤2.5 mIU/L with or without l-T4 treatment; to calculate T0-TSH cut-offs that best precon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Increasing evidence emphasizes an elevated risk of adverse gestational and neonatal outcomes induced by subclinical hypothyroidism in women during the early gestational period. Particularly, the risk of pregnancy-specific complications has been increased in TPOAb-positive women having serum TSH levels exceeding 2.5 mIU/L, especially in those with serum TSH levels greater than 4.0 mIU/L [28]. Unfortunately, results of randomized clinical trials revealed that thyroid hormone supplementation is unsuccessful in the prevention of adverse pregnancy outcomes in women with AITD.…”
Section: The Delicate Thyroid Equilibrium In Pregnancymentioning
confidence: 99%
“…Increasing evidence emphasizes an elevated risk of adverse gestational and neonatal outcomes induced by subclinical hypothyroidism in women during the early gestational period. Particularly, the risk of pregnancy-specific complications has been increased in TPOAb-positive women having serum TSH levels exceeding 2.5 mIU/L, especially in those with serum TSH levels greater than 4.0 mIU/L [28]. Unfortunately, results of randomized clinical trials revealed that thyroid hormone supplementation is unsuccessful in the prevention of adverse pregnancy outcomes in women with AITD.…”
Section: The Delicate Thyroid Equilibrium In Pregnancymentioning
confidence: 99%
“… 3 Actually, over 30% of women with hypothyroidism (Hypo-HT) and euthyroidism-HT (Eu-HT) have TSH greater than 2.5 mIU/L in early pregnancy, 19.7% of women with Hypo-HT and 10.1% of women with Eu-HT have TSH higher than 4.0 mIU/L (P < 0.05). 4 To prevent/reduce the risk of thyroid insufficiency inducing adverse pregnancy outcomes such as LGA during early pregnancy, preconception thyroid function optimization for women with Hashimoto thyroiditis (HT) through levothyroxine sodium is strongly suggested by guidelines. 5 Second, there is a lack of evaluation data on serum ferritin levels.…”
Section: Dear Editormentioning
confidence: 99%